Research of the Visual Measurement Method of Gear Tooth Profile Total Deviation - Wang Ning; Duan Zhenyun; Zhao Wenhui; Du Po; Duan Boqiang (Jixie chuandong)
Aiming at the measuring difficulty of small modulus gear,a measuring method of gear tooth profile total deviation based on machine vision is proposed. On the basis of building measurement vision system,firstly,processing gear digital image with Gaussian filter and edge extraction,then the sub-pixel edge of gear tooth profile is obtained. Because the influence of gear center to tooth profile total deviation is relatively sensitive,by means of radius constraint data to fit round hole center in calibration disc,more accurate center position is obtained. Finally,on the basis of establishing mathematical model to realize tooth profile total deviation measurement. Through the experiment,the measurement result of measuring method and three coordinate measuring machine have higher consistency,the maximum absolute error is less than 3 μm,and the effect of gear position center error on the tooth profile total deviation is one quarter of its error value. The experimental results show that adopting measuring method can accurately reflect the gear tooth profile total deviation,and meeting the requirements of measurement precision reach micron level.